A comprehensive comparison between low and medium temperature application refrigerants at a two-stage refrigeration system with flash intercooling. (October 2019) - Mancuhan, Ebru
Highlights: Optimization method was presented for a two-stage system with flash intercooling. System uses different refrigerants at low and medium temperature applications. Effects of low and high GWP refrigerants on optimum Pint and COPmax were investigated. The COPmax of natural refrigerants' are higher than the synthetic refrigerants'. Abstract: The aim of this paper is to maximize the performance of a refrigeration system with flash intercooling using different refrigerants. Its optimum operating parameters were determined in medium and low temperature applications through a theoretical analysis according to their respective refrigerants R717, R134a, R152a and R290, R404A, R507. The theoretical analysis of each refrigerant is done in terms of different operating conditions specific to their thermo-physical properties. The intermediate pressure is optimized with respect to the evaporation (TE ) and condensation (TC ) temperatures for all refrigerants, and their performance (COP) and second law efficiency values were maximized. The linear regression method is also used to derive three correlations of optimum intermediate pressure (POPT, int ), maximum values of COP and second law efficiency with TE and TC . The analysis indicates that increasing TE and TC increases POPT, int in low and medium temperature applications. In low temperature applications, R507A system has the highest POPT, int values and R290 system has the lowest POPT, int values. R290 was discovered to have better performance than the R404A and R507A systems in terms of COPmax (1.81) and GWP (11) when TE and TC are −35 °C and 40 °C. Similarly, R717 and R152a systems have the highest and lowest POPT, int values respectively in medium temperature applications. R717 was discovered to have the highest COPmax (2.65) and the most environmentally friendly (GWP (0)) relative to R134a and R152a when TE and TC are −20 °C and 40 °C.